TSS: A two‐party secure server‐aid chunking algorithm. (21st September 2021) - Tian, Wenlong; Li, Ruixuan; Xu, Zhiyong
Abstract: Chunking is one of the most important processes in a secure deduplication system. It determines the deduplication ratio, metadata size, and the encryption key number. Existing chunking algorithms can be categorized as client‐side chunking algorithm and the server‐aid chunking algorithm. Although the former one can directly be applied into the secure deduplication, it ignores the management overhead caused by the metadata size and encryption key number. Thus, the conventional server‐aid chunking algorithm is proposed. However, it is not secure because the interaction between the client and the server is based on the plaintext. Thus, we propose a two‐party secure server‐aid chunking algorithm, TSS. It supports the secure server‐aid interaction and reduces the metadata size and the encryption key number in the secure deduplication with a comparable deduplication ratio. The theoretical proof and experimental results show that our method outperforms the state‐of‐the‐art chunking algorithm, elastic chunking algorithm.